Long-term complications of different porous orbital implants: a 21-year review. Issue 5 (29th July 2016) - Lin, Chao-Wen; Liao, Shu-Lang
Abstract : Aims: To analyse the long-term outcomes of different types of orbital implant and the results of dermis fat graft for the management of large-area implant exposure. Methods: Retrospective case series. From 1994 to 2015, 256 patients who received primary implantation after enucleation or evisceration and were followed up for an average of 108.9 months were recruited. Detailed characteristics of patients, including previous surgery or trauma, surgical indications and methods, pegging procedure, and implant types were collected. The long-term outcomes were recorded. For patients with extensive implant exposure (diameter of tissue defect >2 cm), implant removal and dermis fat graft were performed. Results: The risk factors for implant exposure included eviscerated globes and pegged implants. The exposure rates were higher (24.7% in hydroxyapatite (HA), 23.5% in bioceramic and 76.5% in Medpor) as compared with those in previous reports. The average times to exposure were 67.4 months in HA, 52.5 months in bioceramic and 73.4 months in Medpor implants. Among the cases with implant exposure, late exposure (>2 years after operation) accounted for 67% of cases. Thirty eyes with large-area exposure were managed with dermis fat grafts. Twenty-four cases were successfully treated with single surgery. The other six cases developed fornix loss and required additional reconstruction with full thickness skin graft. Conclusions: Late exposures of porous orbital implants were noted during long-term follow-up. The causes of implant exposure may be associated with pegging procedures and evisceration. The implantation of dermis fat can be an effective procedure for the management of large-area implant exposure.